Factors influencing employee satisfaction with retirement benefits in Malaysia - Ismail, Fadillah; Kang, Hee Yong (Journal of Islamic, Social, Economics and Development, 2025)
This research to identify some of the factors that impact on employee perception to retirement benefits in Malaysia. These major dimensions are adequacy of benefits, financial understanding, and health care assistance. The study establishes that low remunerative accumulations for retirement and poor health care facilities cause general employee discontent. The research reveals that ordinations to advance benefit schemes, modifying participant’s financial education, and incorporating healthcare support are critical interventions needed to meet retirees’ requirements for satisfaction.